Structural Dynamics Analysis of a Large Aperture Space Telescope Based on the Linear State Space Method - Bin Ma; Zongxuan Li; Lin Li; Yunfeng Li; Youhan Peng; Shuhui Ren; Qingya Li; Jiakun Xu (Sensors)
The linear state space model of an optical remote sensing camera with an aperture of φ572 mm was established using the structural dynamics and linear state space theory. Modal reduction was carried out using the balanced reduction method. Combined with the controllable and observability matrix, the model order was reduced. To obtain the frequency response curve between the excitation input point and the response output point, we performed a frequency response analysis with the reduced state space model. The initial frequency response curve was plotted and compared with the response curves of the DC gain method and the balanced reduction method. The accuracy and rationality of the simulation analysis were verified by dynamic tests. The balanced reduction method under state space representation provides a new method for studying the dynamics of lightweight opto-mechanical structures. It can characterize the inherent properties of the system by using the reduction model and has higher computational efficiency, which is helpful to analyze the frequency response characteristics of complex linear systems quickly and accurately.